1998
DOI: 10.1210/jcem.83.8.5039
|View full text |Cite
|
Sign up to set email alerts
|

The Low Dose (1-μg) Adrenocorticotropin Stimulation Test in the Evaluation of Patients with Suspected Central Adrenal Insufficiency

Abstract: Currently, the most popular test for adrenal insufficiency is the conventional rapid ACTH stimulation test (250 microg ACTH). This method is quick and safe, but incorporates a dose of ACTH that is supraphysiological and capable of transiently stimulating the adrenal cortex in many patients with documented central adrenal insufficiency. In recent years, several investigators have published substantial evidence for a more sensitive ACTH stimulation test using a lower dose of ACTH (1 microg). Further analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
1
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(95 citation statements)
references
References 14 publications
1
90
1
3
Order By: Relevance
“…The low-dose (1 mg) ACTH test has recently been introduced and proved to be sensitive in revealing partial adrenal insufficiency by providing physiological adrenocortical stimulation (5,6). The results of the low-dose (1 mg) ACTH test correlate closely with those of the reference test for the function of the HPA axis (7), and are superior to the standard (250 mg) ACTH test (8). However, the literature remains controversial about the cut-off point representing a normal adrenal response to 1 mg ACTH, and about the sensitivity of the low-dose (1 mg) ACTH test in the diagnosis of secondary hypoadrenalism (9).…”
Section: Introductionmentioning
confidence: 99%
“…The low-dose (1 mg) ACTH test has recently been introduced and proved to be sensitive in revealing partial adrenal insufficiency by providing physiological adrenocortical stimulation (5,6). The results of the low-dose (1 mg) ACTH test correlate closely with those of the reference test for the function of the HPA axis (7), and are superior to the standard (250 mg) ACTH test (8). However, the literature remains controversial about the cut-off point representing a normal adrenal response to 1 mg ACTH, and about the sensitivity of the low-dose (1 mg) ACTH test in the diagnosis of secondary hypoadrenalism (9).…”
Section: Introductionmentioning
confidence: 99%
“…However, during the last years it has been reported that the 250 mg ACTH stimulation test is a supraphysiological test and it may cause misdiagnosis in secondary and primary adrenal failure (8 -11). The sensitivity of the low dose (1 mg) test (LDT) is higher than that of the standard dose (250 mg) test (SDT) in the assessment of the hypothalamo -pituitary-adrenal (HPA) axis, particularly in pituitary disease (12,13). There are not enough data evaluating adrenal steroidogenesis, particularly P450c17a enzyme activity, with LDT in women with PCOS.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, a lower dose of ACTH (1 µg) is being used as a sensitive test in patients with subtle adrenal dysfunction, which is considered to be the test of choice in the evaluation of adrenal function in pituitary diseases 20 . Lower doses are considered to be more physiological, avoiding a hyper-stimulus, and the results obtained are similar to hypoglycemia induced by insulin or a great physical stress 14 .…”
Section: Discussionmentioning
confidence: 99%